Five reasons for using social media among young terror survivors: Results from the Utøya study. (July 2018) - Nilsen, Lisa Govasli; Hafstad, Gertrud Sofie; Staksrud, Elisabeth; Dyb, Grete
Abstract: This study explores how young survivors experienced social media usage after the 2011 terror attack at Utøya, Norway. In total, 112 interviews with survivors were conducted 14–15 months post-terror, and analyzed using thematic analysis. Five reasons for social media usage were identified: 1) exchange of information, 2) giving and receiving social support, 3) mourning, 4) performing different symbolic actions, and 5) partaking in debates and discussions pertaining to the terror. Our informants described how their participation in online debates existed in a space between their personal stories and the public narrative surrounding the July 22 attacks. As unedited and easily accessible platforms, social media had characteristics that differentiated them from other arenas in which the survivors were communicating about the terror attack. The potential for receiving support was described as massive, because social media were perceived as platforms where the threshold for reaching out was low. However, participants felt that although social media usage enabled survivors to take control when presenting their own narratives, it also took some of their control away as their posts could be misinterpreted. They also felt that they were unable to protect themselves from information and opinions that they found distressing. Highlights: Young terror survivors use social media to exchange information and support. Social media are used to perform symbolic actions and to mourn deceased peers. Social media are used to participate in debates outside traditional media outlets. Social media give terror survivors a feeling of control over their own narratives. It is difficult for survivors to shield themselves from harmful communication.